Intermediates of Prothrombin Activation Induce Intracellular Calcium Mobilization in Rat Aortic Smooth Muscle Cells - Kaufmann, Roland; Hoffmann, Jutta; Ramakrishnan, Vanitha; Nowak, Götz (Thrombosis and Haemostasis, 1998)
While effects of alpha-thrombin have been well characterized in different cell types, the biological function of intermediates of prothrombin activation is still undefined. Meizothrombin could be shown to be a potent agonist for vascular contraction which seems to be mediated by an interaction with the vascular smooth muscle. To explore this effect at intracellular signaling level, we used rat aortic smooth muscle cells and investigated the effect of the intermediates formed by cleavage of human prothrombin with ecarin, the prothrombin activator from Echis carinatus venom, on mobilization of free intracellular calcium. The ecarin-activated prothrombin induced very rapidly transient calcium mobilization in SMC´s comparable to that observed with alpha-thrombin. We conclude that meizothrombin/ meizothrombin desF1 (MT/MT desF1) are the most likely candidates for this effect. Furthermore, our results suggest the involvement of PAR-1-type thrombin receptors in MT/MT desF1-induced calcium signaling in rat aortic smooth muscle cells.